TINDAK TUTUR KOMISIF PADA WACANA DIALOG CALON WALIKOTA PARIAMAN (IJP: Indra Jaya Piling) - Zona Rida Rahayu (JELISA (Jurnal Edukasi dan Literasi Bahasa), 2020)
Commissive speech acts in discourse dialogue with the candidates for mayor of Pariaman -IJP- sympathizers aimed at explaining the form of speech act commissive and contextual explanation. Commissive speech act is used in dialogue with sympathizers in the form of speech promise and offer something. But the speakers did not use the speech act commissive dengna form of oath. Commissive speech acts speech acts are used only with the form of promises and offers, while the speech act with a form of oath was not found. In utter promises and offers something of speakers seem to be careful in communicating with supporters. This is done so that the speaker hearer does not feel offended or deceived by the utterances of speakers. Because the purpose of a dialogue with the speakers of sympathizers to steal sympathetic and settled on the speakers as the prospective head region. In addition to speech acts speech acts commissive also found another use of a speaker and hearer in the dialogue that is assertive speech act with the report form, mentions, and shows as well as expressive speech acts in the form of criticism.